Prehistoric times - Coronet Instructional Media (Firm). (Northbrook, Illinois Coronet MTI Film & Video, 1976)
Uses dioramas, actual fossil remains, examples of terrain, and models to help reconstruct the vast eras that came and passed before the time of human existence.
Distributed by International Book Center.
Consultants, Charles Shabica, Ron Tyner.
Keywords: Anthropology, Prehistoric; Prehistoric peoples; Geology